Diffuse Pulmonary Ossification in a Dog - Goveia Martins, Ana Flávia; Cleyber de Oliveira Júnior, Washington; Maria Brianezi Dignani de Moura, Veridiana (Acta Scientiae Veterinariae, 2023)
Background: Diffuse pulmonary ossification is an unusual condition, in which typical osseous tissue is found in the lung. Although it is more studied in humans, it is also important in veterinary medicine due to its occurrence in canines and wild species. On macroscopic examination, it typically presents itself as protruding and white formations. The conclusive diagnosis is achieved by microscopic analysis. There are no proofs about its etiology, with many different theories on what would cause it, as well as its occurrence is rare. Therefore, it is intended, with this report, to describe the anatomopathological findings in a dog stricken with diffuse pulmonary ossification. Case: A 13-year-old male Labrador was sent to anatomopathological examination with a history of mast cell tumor, having gone through the extraction of 2 cutaneous nodules, and locomotor disorders, such as arthrosis in all 4 members and pelvic dysplasia. Due to the animal's poor clinical condition and walking difficulty, it was subjected to euthanasia. During the necroscopic exam, the lungs presented, in all their extension, multiple small formations, white in color, of firm consistency, varied sizes and miliary aspect, which raised to the pleural surface. Except for the presence of congestion and pulmonary edema, and a foreign body found in the stomach, there were no other alterations. When submitted to microscopic evaluation, the lung samples, fixed in 10% buffered formalin and decalcified, showed innumerable irregular formations composed by osteocytes arranged in gaps, distributed in concentric layers. There was no associated inflammatory response. On a few sections of the parenchyma, there was narrowing of respiratory bronchioles in areas close to the osseous structures. Based on the cell analysis, the diagnosis of diffuse pulmonary ossification was confirmed. Discussion: The development of bone tissue in lung parenchyma has been described in different ways in the literature, and in many species, such as dogs, wild animals and even humans. In that regard, it is essential to separate this process from that resulting from calcification, which is consistent with deposition of calcium and phosphor in the tissue, whereas ossification involves the presence of mature bone cells, although it is not uncommon for them to occur together. There are 2 known forms of the disease, the nodular pattern, which presents itself as small round nodules, and the dendriform shape, in which the osseous tissue is arranged linearly and contains bone marrow. The formations seen in this animal’s lungs were characteristic of the nodular aspect, which is the most common in animals, meanwhile the linear shape is mostly associated with humans. The pathogenesis around this sickness is uncertain, possibly being a consequence of metaplastic processes brought on by pulmonary fibrosis or senescence conditions, which are a very common finding. The symptomatology is diverse among the patients, who may be asymptomatic or present respiratory difficulty. The ante mortem diagnosis is of rare occurrence given that most cases are only identified during the necroscopic exam. Thus, in view of the few reports of pulmonary ossification in animals, the description of this case is relevant to veterinary medicine due to its contribution with knowledge around the anatomopathological aspects, clinical signs and etiology of diffuse pulmonary ossification. Keywords: lung, bone, osteocyte, microlithiasis. Título: Ossificação pulmonar difusa em um canino Descritores: pulmão, osso, osteócito, microlitíase.